THE PLACE AND ROLE OF LEGAL TECHNIQUE IN LEGAL CREATIVITY - Shukhrat Kuchimov (International Journal of Innovative Technologies in Social Science, 2022)
This article analyzes the place and role of legislative technique in legal creativity, the content and essence of legislative technique. Proposals and recommendations on the development of legislative techniques are given.